2022
DOI: 10.1038/s41366-022-01250-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review with meta-analyses of the relationship between recurrent binge eating and sleep parameters

Abstract: Background: Sleep problems are known to compound the negative effects of other health issues, such as eating disorders and the associated behaviour of binge eating. Previous studies suggested associations between binge eating and sleep problems, but the strength of the relationship is unknown. Methods: We conducted a systematic review with meta-analyses examining the relationship between binge eating and sleep parameters. We searched for studies in Scopus, PubMed, and PsycInfo. The quality of evidence, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…In addition to the relatively high incidence of poor sleep quality, noteworthy findings include the relationship between sleep quality and disordered eating within a purely community sample. The current results align with a recent meta-analysis that binge eating was specifically related to worse sleep [24] but also expand to other related symptoms that may be more widespread, including overall eating psychopathology, loss of control eating, and subjective binge episodes. Yeh & Brown [27] found people with overweight and obesity reported delayed sleep onset and reduced sleep duration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to the relatively high incidence of poor sleep quality, noteworthy findings include the relationship between sleep quality and disordered eating within a purely community sample. The current results align with a recent meta-analysis that binge eating was specifically related to worse sleep [24] but also expand to other related symptoms that may be more widespread, including overall eating psychopathology, loss of control eating, and subjective binge episodes. Yeh & Brown [27] found people with overweight and obesity reported delayed sleep onset and reduced sleep duration.…”
Section: Discussionsupporting
confidence: 89%
“…The literature suggests relationships between different forms of disordered eating diagnoses (e.g., anorexia nervosa) and poor sleep [18]. Da Luz and authors conducted a systematic review [24] of studies including clinical and community participants with binge eating behaviors, finding that participants with binge eating behaviors exhibited poorer sleep quality compared to participants with no binge eating patterns; however, the authors did caution lack of validated sleep measures as a limitation within the literature. In a clinical sample of individuals with loss of control eating following weight-loss surgery, participants completed measures of sleep quality, disordered eating, health-related quality of life, and physical and mental health functioning [23].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that objective binge eating is significantly related to sleep quality aligns with the conclusions of a recent meta-analysis which found that people who engage in binge eating reported substantially worse sleep quality compared to those who do not engage in binge eating [ 16 ]. It is plausible that certain behavioral features of binge eating contribute to worse sleep quality.…”
Section: Discussionsupporting
confidence: 83%
“…Recent literature reviews and a meta-analysis have supported the empirical link between sleep and disordered eating behaviors [ 14 16 ]. The nature of this relationship is likely bidirectional, such that sleep disturbance increases the risk of disordered eating behavior and, in turn, disordered eating behavior increases the risk of disturbed sleep [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep seems to also play an important role in eating disorders, including BED [86] and BED. For example, a systematic review by da Luz et al (2023) [87] found that people who binge eat exhibit poorer overall sleep quality compared to people who do not binge eat, and may have more daytime sleepiness, insomnia, and difficulty falling asleep. BED has even been proposed as a possible circadian disorder [88].…”
Section: Discussionmentioning
confidence: 99%